Pastoralism in Africa : past, present, and futures - Bollig, Michael; Schnegg, Michael; Wotzka, Hans-Peter (Berghahn, 2013)
Pastoralism has shaped livelihoods and landscapes on the African continent for millennia. Mobile livestock husbandry has generally been portrayed as an economic strategy that successfully met the challenges of low biomass productivity and environmental variability in arid and semi-arid environments. This volume focuses on the emergence, diversity, and inherent dynamics of pastoralism in Africa based on research during a twelve-year period on the southwest and northeast regions. Unraveling the complex prehistory, history, and contemporary political ecology of African pastoralism, results in.